2021
DOI: 10.1101/2021.07.08.21259776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of SARS-CoV-2 mRNA Vaccines for Preventing Covid-19 Hospitalizations in the United States

Abstract: BackgroundAs SARS-CoV-2 vaccination coverage increases in the United States (US), there is a need to understand the real-world effectiveness against severe Covid-19 and among people at increased risk for poor outcomes.MethodsIn a multicenter case-control analysis of US adults hospitalized March 11 - May 5, 2021, we evaluated vaccine effectiveness to prevent Covid-19 hospitalizations by comparing odds of prior vaccination with an mRNA vaccine (Pfizer-BioNTech or Moderna) between cases hospitalized with Covid-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 29 publications
9
83
3
1
Order By: Relevance
“…The findings of this study complement and expand on those of other recent real-world studies that have indicated reduced COVID-19 vaccine protection for some IC patient groups [13][14][15][16][17][18][19][20][21]. In a US study of hospitalized patients, Tenforde et al found that of the 45 hospitalized COVID-19 cases, 44% were IC; mRNA VE against COVID-19 hospitalization was estimated at 63% for those who were IC and 91% among those who were not [13].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this study complement and expand on those of other recent real-world studies that have indicated reduced COVID-19 vaccine protection for some IC patient groups [13][14][15][16][17][18][19][20][21]. In a US study of hospitalized patients, Tenforde et al found that of the 45 hospitalized COVID-19 cases, 44% were IC; mRNA VE against COVID-19 hospitalization was estimated at 63% for those who were IC and 91% among those who were not [13].…”
Section: Discussionsupporting
confidence: 83%
“…Currently, there is limited information in the published literature on whether a suboptimal immune response to the COVID-19 mRNA vaccines among those with IC conditions [8][9][10][11][12] leads to reduced vaccine effectiveness (VE). Some recently conducted real-world studies that included subpopulations with IC conditions have found that while the COVID-19 vaccines were effective in this patient group, VE against SARS-CoV-2 infection, symptomatic illness, and COVID-19-related hospitalization was lower than observed in the general population, with VE ranging from 63% to 90% [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Immune response is also affected by malignancies, organ and stem cell transplants, immunosuppressive medications, human immunodeficiency virus infection, and primary immunodeficiencies. 1 However, there is a much larger group of individuals who fail to respond adequately to vaccination and to whom none of these classic immunosuppression conditions apply. Recent research has provided important new clues about how to help them.…”
Section: Shoring Up Vaccine Efficacymentioning
confidence: 99%
“…Concerns about the robustness of the vaccine-induced immune response in vulnerable populations 57 have prompted the Centers for Disease Control and Prevention (CDC) to recommend an additional dose for immunocompromised patients, 8 while concerns about the durability of response have prompted discussion of booster doses of vaccine. 9 The implications for patients receiving maintenance dialysis remain unclear at this time.…”
Section: Introductionmentioning
confidence: 99%
“…1 The three vaccines currently authorized for use by the Food and Drug Administration, either with approval or emergency use authorization, are all highly effective at preventing death and serious illness in the general population. [2][3][4] Concerns about the robustness of the vaccine-induced immune response in vulnerable populations [5][6][7] have prompted the Centers for Disease Control and Prevention (CDC) to recommend an additional dose for immunocompromised patients, 8 while concerns about the durability of response have prompted discussion of booster doses of vaccine. 9 The implications for patients receiving maintenance dialysis remain unclear at this time.…”
Section: Introductionmentioning
confidence: 99%